The Influence of Motivation, Work Environment, and Transformational Leadership on the Performance of Operating Room Nurses - Merry, Merry; Hutapea, Ruth N.; Bernarto, Innocentius (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The purpose of this study is to determine the influence of motivation, work environment, and transformational leadership on the performance of operating room nurses. The data collection method in this study was by using questionnaires. The total number of respondents was 48 nurses at Cengkareng Hospital. This study is a census study. Data analysis method with Partial Least Squares Modeling approach. The results showed that motivation, work environment, and transformational leadership positively affect nurse performance.